Brain executive laterality and hemisity - Morton, Bruce Eldine (Personal Neurosci, 2020)
Brain laterality refers to the asymmetric location of functional elements within the bilateral brain of animals and humans. Thus far, five lateralized functions have been recognized in humans: handedness, language ability, spatial skills, facial recognition, and emotion recognition. Recently, a sixth asymmetric functional element bearing on personality has been discovered. It is the larger side of the split bilateral anterior cingulate cortex (ACC). This appears to be the final output element of the executive system of which, by logic, there can be only one. Which side is somewhat larger varies among the general population in a seemingly idiosyncratic manner, yet with a genetic basis because true-breeding lineages exist. Here, hemisity is binary measure where a person is inherently born either right brain or left brain oriented. This is determined by nine statistically robust sets of four biophysical tests, none of which depend upon personality, and five behavioral questionnaires. Crucially these hemisity methods have been validated by the Magnetic Resonance Imaging (MRI)-based discovery that the larger side of the ACC is on the same side as one’s hemisity, making MRI the primary standard for hemisity determination (r = 0.96). There are at least 30 measurable differences in individual characteristics and behaviors between those persons whose hemsity is on the right compared to those with it on the left. The hemisity of 2929 individuals was determined by these methods. Large groups included 1428 junior and senior high schools students both in Hawaii and Utah. There were somewhat comparable numbers present for both types of hemisity. Hemisity of individuals was found stable from infancy to old age. There was no relation between hemisity and handedness. Larger corpus callosum (CC) size of male or female subjects was larger in right brainer that in left brainers. Twin studies demonstrate that CC size is inherited. Thirty-eight percent of individuals of both sexes were right brain oriented, while 62% of individuals of both sexes were left brain oriented. In pairings, there were more than twice as many couples with opposite hemisity. Of these couples, the right brain male and females were dominant. Reproductive outcomes of these were “Like father like son, Like mother like daughter.”